Peony Seed Products as Emerging Functional Foods: Bioactive Compounds, Extraction Technologies, and Future Directions - Nabila Jabbar (Indus Journal of Social Sciences, 2025)
Peony-derived products, especially peony seed oil (PSO), are garnering increasing attention due to their notable nutritional, therapeutic, and commercial potential. Herbaceous peonies (Paeonia lactiflora Pall.), historically cultivated in China for their ornamental and medicinal properties, have recently emerged as a dual-purpose crop. Beyond their traditional use for bioactives such as paeonol and paeoniflorin, the seeds once considered industrial waste are now recognized as a rich source of unsaturated fatty acids, essential amino acids, polyphenols, stilbenoids, and minerals. Among these, PSO stands out for its exceptionally high content of α-linolenic acid and γ-tocopherol, which contribute to its potent antioxidant capacity. Modern extraction technologies, including solvent-based methods, ultrasound-assisted extraction (UAE), and microwave-assisted extraction (MAE), have significantly improved the yield and bioactivity of PSO constituents. These techniques facilitate the efficient recovery of functional compounds while maintaining their structural integrity. Extensive pharmacological studies have demonstrated that PSO possesses a wide range of biological activities, including antioxidant, anti-inflammatory, antidiabetic, hypolipidemic, and hepatoprotective effects. Recent evidence also highlights its potential role in ameliorating metabolic disorders such as non-alcoholic fatty liver disease (NAFLD), positioning PSO as a promising candidate in functional food and nutraceutical development. Due to its safety and nutritional value, PSO has been approved as a new food resource by Chinese regulatory authorities, further stimulating research into its comprehensive health effects, molecular mechanisms, and industrial scalability. However, challenges remain in optimizing extraction efficiency, ensuring product stability, standardizing cultivation practices, and validating health claims through clinical studies. Future research should prioritize the development of eco-friendly production systems, quality control standards, and diversified applications in food, pharmaceutical, and cosmetic industries. The growing body of evidence supports PSO as high-value plant oil with significant implications for human health, economic development, and sustainable agriculture.